2010
DOI: 10.1007/978-3-642-14379-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Energy Theft in the Advanced Metering Infrastructure

Abstract: Abstract. Global energy generation and delivery systems are transitioning to a new computerized "smart grid". One of the principle components of the smart grid is an advanced metering infrastructure (AMI). AMI replaces the analog meters with computerized systems that report usage over digital communication interfaces, e.g., phone lines. However, with this infrastructure comes new risk. In this paper, we consider adversary means of defrauding the electrical grid by manipulating AMI systems. We document the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(105 citation statements)
references
References 5 publications
0
103
0
2
Order By: Relevance
“…Moreover, if the smart meter is physically tampered, the hackers can capture optical port protocol used to communicate with smart meters. If the smart meter is opened, they will put a reader device on this port to capture the other password for other protocols [13]. Without firmware integrity protections in smart meters, meter storage can also be tampered.…”
Section: Threats a Smart Metersmentioning
confidence: 99%
“…Moreover, if the smart meter is physically tampered, the hackers can capture optical port protocol used to communicate with smart meters. If the smart meter is opened, they will put a reader device on this port to capture the other password for other protocols [13]. Without firmware integrity protections in smart meters, meter storage can also be tampered.…”
Section: Threats a Smart Metersmentioning
confidence: 99%
“…It does this by recursively breaking down a goal into finer-and finergrained subgoals and finally to a set of attacks that achieve the original goal. An example attack tree that formed the genesis of this work [5] is shown in Figure 1. The root specifies the end goal, committing energy fraud by forging the energy usage information reported to the utility.…”
Section: Approachmentioning
confidence: 99%
“…Academic and industrial pen-testing efforts have found flaws in smart meter hardware [13], firmware [14] and network protocols [5]. Recently, Pacific Gas and Electric (PG&E) has experienced problems with measurement accuracy and meter network connectivity in their 5 million meter deployment, one of the largest in the US [15].…”
Section: A Ami Security Concernsmentioning
confidence: 99%
“…A good example of such issues can be seen in the domain for Smart Metering. In the Netherlands the government intended to make a compulsory roll out of meters as part of a national energy reduction plan, but this was curbed when privacy issues were raised [12]. The scheme is now voluntary and the issues of recording of device level data in the home can be seen to raise other privacy and trust risks for consumers [28].…”
Section: Introductionmentioning
confidence: 99%